Severe Necrotizing Adenovirus Tubulointerstitial Nephritis in a Kidney Transplant Recipient. (28th August 2013) - Parasuraman, Ravi; Zhang, Ping L.; Samarapungavan, Dilip; Rocher, Leslie; Koffron, Alan
Abstract : Adenoviruses (AdV) are emerging pathogens with a prevalence of 11% viruria and 6.5% viremia in kidney transplant recipients. Although AdV infection is common, interstitial nephritis (ADVIN) is rare with only 13 biopsy proven cases reported in the literature. We report a case of severe ADVIN with characteristic histological features that includes severe necrotizing granulomatous lesion with widespread tubular basement membrane rupture and hyperchromatic smudgy intranuclear inclusions in the tubular epithelial cells. The patient was asymptomatic at presentation, and the high AdV viral load (quantitative PCR>2, 000, 000 copies/mL in the urine and 646, 642 copies/mL in the serum) confirmed the diagnosis. The patient showed excellent response to a combination of immunosuppression reduction, intravenous cidofovir, and immunoglobulin therapy resulting in complete resolution of infection and recovery of allograft function. Awareness of characteristic biopsy findings may help to clinch the diagnosis early which is essential since the disseminated infection is associated with high mortality of 18% in kidney transplant recipients. Cidofovir is considered the agent of choice for AdV infection in immunocompromised despite lack of randomized trials, and the addition of intravenous immunoglobulin may aid in resolution of infection while help prevention of rejection.